3D printed bismuth oxide‐polylactic acid composites for radio‐mimetic computed tomography spine phantoms. Issue 6 (26th October 2020) - Arnold, John; Sarkar, Korak; Smith, Damon
Abstract: Polylactic acid (PLA) composite filaments with varying concentrations of bismuth oxide microparticle additives were fabricated for use with commercially available fused filament fabrication (FFF) printing systems for the production of spine phantoms that mimic the radiopacity of bone. Thermal analysis showed that the additives had limited impact on the glass transition temperature and melting point of the filaments, allowing for their use in commercial FFF systems with standard printer settings. The ultimate strength of the printed test specimens was found to reduce slightly when bismuth oxide was added in high concentrations, with a moderate reduction of 12% compared to PLA at the highest concentration of 30 wt%. The modulus of the specimens increased by up to 24% with the addition of the additive. The radiopacity of specimens printed with the composite filaments were measured by X‐ray microcomputed tomography (micro‐CT) and clinical computed tomography (CT). The CT number was found to increase by approximately 196 HU per wt% of bismuth oxide added to the filaments. A phantom model of a cervical spine deformity was successfully printed by FFF with a composite filament which was calibrated to mimic the radiopacity of cervical and cortical bone. The results indicate that the composite filaments have direct applicability for the production of phantoms used for education and preoperative planning.